Transmission enhancement in chalco-halide glasses for multiband applications - Ledemi, Yannick; El Amraoui, Mohammed; Messaddeq, Younes [UNESP] (Optica Publishing Group, 2014)
The potential of clear Ga2S3-GeS2-CsCl based sulfide glasses transparent up to 11.5 μm to be used as new optical material for multispectral applications has been investigated. The addition of large amount of chlorine ions – above 40 mol.% of CsCl – into the chalcogenide vitreous network in order to produce colorless glasses results in a drastic increase of their water contamination. We report for the first time, to the best of our knowledge, the purification of cesium chloride CsCl by dynamic distillations under vacuum in order to reduce water and hydroxyl group contamination before complete melting of the glass. Besides, sulfur purification by dynamic and static distillations was also performed in the implemented method. The obtained glasses were then characterized by UV-visible and infrared (FTIR) spectroscopies, by electron probe microanalysis (EPMA), thermal analysis (DSC), and their refractive indices in the visible and near infrared ranges were also measured. A large improvement of the glass transmission spectrum has been achieved with an estimated reduction of about 45 times of the OH and H2O content and 60 times of the SH content. The glass thermal molding ability and chemical durability with and without protective coating have been tested to probe their potential for fabrication of complex optics.